Relationship between changes in exercise habits and self-efficacy before and during a pandemic of COVID-19 among health care workers - FUKUEI, Tatsuya; ONODA, Tetsuya; AISHITA, Yukari; UTO, Yoshihiro (Journal of Physical Therapy for Prevention, 2024)
Objective: This study examined the relationship between changes in exercise habits and self-efficacy before and during the COVID-19 pandemic among health care workers. Methods: The study included 77 participants who took part in the 2019 and 2021 Annual Health Surveys. Self-efficacy was assessed using the General Self-Efficacy Scale. Exercise habits were defined as those who exercise at least several times a month. Respondents who reported no exercise habits in 2019 and exercise habits in 2021 were in the increased exercise habit group, respondents who reported exercise habits in both 2019 and 2021 or no exercise habits in both 2019 and 2021 were in the unchanged exercise habit group, and respondents who reported exercise habits in 2019 and no exercise habits in 2021 were in the decreased exercise habit group. Statistical analysis was a repeated-measures analysis of covariance for self-efficacy in 2019 and 2021 in each group. (covariates: age, gender, medical occupation). Results: The increased exercise habit group had significantly higher self-efficacy in 2021 compared to 2019 (p=0.004, F=3.750). The unchanged exercise habit group (p<0.001, F=6.122) and the decreased exercise habit group (p=0.008, F=3.229) had significantly lower self-efficacy in 2021 compared to 2019. Conclusions: Exercise habits changes during the COVID-19 pandemic might be related to self-efficacy as well.